Innovative Environmental Strategy for Sustainable Development - Kaletnik, Grygorii; Lutkovska, Svitlana (European Journal of Sustainable Development, 2020)
This article investigates the development of an innovative strategy for environmentally sustainable development. The breakthrough strategy has been found to be an activity-based structure and system of activities to accelerate growth. It has been found out that, in form and substance, all practical business development strategies depend on specific internal and external circumstances. It is proved that when developing breakthrough strategies for socio-economic development of a country, it is necessary to be guided by certain methodical techniques or rules, namely: scientific and applied justification; identifying and progressively improving an attractive value proposition; development and continuous improvement of the business model; drawing up and implementing an action plan; forming the focus of all participants in the breakthrough strategy on the achievement of strategic goals. The main products of the breakthrough strategy are found to be the organizational mission, value proposition, business model and set of projects and programs that form the breakthrough strategy cycle [2, 4]. It is found that there are different types of breakthrough strategies, among them the following: 1) storming strategy; 2) lagging behind in leaders; 3) expansion of horizons; 4) change of form [3]. Breakthrough strategies in the industry include the introduction of modern innovative industrial technologies on the basis of support for the development of high-tech industries (increasing production of domestic aviation and space technology, instrumentation, electronic technology, nanotechnology, medical technology), harnessing the potential of Ukraine to expand medium-tech production automotive, newest rolling stock and other railway equipment), Stim fostering the creation of new innovation development poles (creation of innovation clusters in the regions of Ukraine)[4]. It is proved that sustainable environmental development is impossible without the formation and use of appropriate management potential, that is, the ability of managers is qualified to "launch" all other potentials. It has been determined that the goal of green economy development should be to achieve a higher level of well-being while simultaneously solving resource-ecological and social problems. Keywords: strategy, innovation, environmental security, sustainable development.